2007
DOI: 10.1364/ol.32.000942
|View full text |Cite
|
Sign up to set email alerts
|

Comment on "Pushing the hyperpolarizability to the limit"

Abstract: It is shown that energy/length scaling complicates maximizing the first hyperpolarizability of a single electron as a function of the potential. A more transparent formula for this hyperpolarizability is given. Examining this formula demonstrates that Zhou et al.(1) have not proved that modulated conjugation results in large hyperpolarizability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…1(b)(ii)]. Such a change is expected a priori from previous work [16] to make no significant difference to γ int as it is far from the region where ψ 0 and ψ 1 are large. For this well-like potential, we performed a maximization, adjusting A 2 , x 1 , and x 2 while fixing the outer walls to have a large slope (A 3 = 100).…”
Section: Resultsmentioning
confidence: 77%
“…1(b)(ii)]. Such a change is expected a priori from previous work [16] to make no significant difference to γ int as it is far from the region where ψ 0 and ψ 1 are large. For this well-like potential, we performed a maximization, adjusting A 2 , x 1 , and x 2 while fixing the outer walls to have a large slope (A 3 = 100).…”
Section: Resultsmentioning
confidence: 77%
“…those near the Fermi surface. This is justified by previous studies [15] that have shown the addition of small rapidly varying perturbations to the potential doesn't affect the hyperpolarizabilities. The ansatz potentials studied in this work, with delta functions and changes in slope at isolated points, all satisfy this criterion.…”
Section: Appendix A: Approximate Analysismentioning
confidence: 63%
“…perpolarizabilities can be completely reconstructed from the ground state wavefunction [15]. Extending this to the N > 1 case, it is easy to see that the hyperpolarizablities can be constructed for this problem as appropriate integrals of the occupied single particle wavefunctions alone.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, since the hyperpolarizability has been shown to depend only on dipole matrix elements and may be derived entirely as a multiple integral of the ground state wavefunction [8], changes in the potential where the ground state wavefunction is large are also irrelevant if they tend not to alter the wavefunction. For example, rapid variations in the potential which approximately average to zero will not significantly affect the hyperpolarizability.…”
Section: Introductionmentioning
confidence: 99%